The educational dimension of pastoral youth service - Dra. Miriam Gallego (Universidad Politécnica Salesiana, 2013)
The educational dimension of pastoral youth service is highlighted by the fact that it is about education on faith. Faith education means taking a young person towards a personal encounter with God. This fact is also known as an experience with God or religious experience. The religious experience favors cognitive and affective development, desire of the absolute, relationships development, commitments with justice, and the construction of a personal life and social history; in this regard, the religious experience turns into an educational one.The evangelist deed in the pastoral youth service, does not occur through isolated actions but through a process, that is, through a set of educational dynamisms that bring the young person to open up to his/her personal and social reality, to search for answers to his/her questions, be active in society, and build a life project. In pastoral ministries each gesture is, at the same time and with the same intensity, an educational event and a proposal of youth's lives about God's mysteries. The pastoral youth service brings educational means -objectives, contents, educational sites, processes, methodologies, people responsible for education, etc.- that can be no doubt evaluated.